Active Control of Slow Light in a Gain-Assisted Plasmon-Induced Transparency Structure - Jianhua Yang; Song Yang; Xiaokang Song; Fang Wu; Li Yu (IEEE Photonics Journal, 2017)
Plasmon-induced transparency (PIT) in a compact plasmonic resonator structure, which consists of a metal– dielectric–metal waveguide with an aperture-coupled square cavity and a slot resonator, is investigated theoretically and numerically. We find the transparency window and the delay of slow light in this structure can be controlled at a fixed wavelength by carefully adjusting the geometrical parameters of the aperture-coupled square cavity. By introducing gain medium into the slot resonator, the transmittance and the group index in transparency window both are dramatically enhanced with optically pumping the medium, and the group delay time can reach to 0.93 ps. In addition, triple PIT effects are also achieved by adding another aperture-coupled cavity and slot cavity, and corresponding slow light also can be dynamically tuned. This study paves a new route toward the realization of highly integrated all-optical circuits and networks, especially for ultrafast switches, optical buffers, lasers, and nanosensors.